Epidemiology of small intestinal atresia in Europe: a register-based study. Issue 5 (29th August 2012) - Best, Kate E; Tennant, Peter W G; Addor, Marie-Claude; Bianchi, Fabrizio; Boyd, Patricia; Calzolari, Elisa; Dias, Carlos Matias; Doray, Berenice; Draper, Elizabeth; Garne, Ester; Gatt, Miriam; Greenlees, Ruth; et al.
Abstract : Background: The epidemiology of congenital small intestinal atresia (SIA) has not been well studied. This study describes the presence of additional anomalies, pregnancy outcomes, total prevalence and association with maternal age in SIA cases in Europe. Methods: Cases of SIA delivered during January 1990 to December 2006 notified to 20 EUROCAT registers formed the population-based case series. Prevalence over time was estimated using multilevel Poisson regression, and heterogeneity between registers was evaluated from the random component of the intercept. Results: In total 1133 SIA cases were reported among 5126, 164 registered births. Of 1044 singleton cases, 215 (20.6%) cases were associated with a chromosomal anomaly. Of 829 singleton SIA cases with normal karyotype, 221 (26.7%) were associated with other structural anomalies. Considering cases with normal karyotype, the total prevalence per 10 000 births was 1.6 (95% CI 1.5 to 1.7) for SIA, 0.9 (95% CI 0.8 to 1.0) for duodenal atresia and 0.7 (95% CI 0.7 to 0.8) for jejunoileal atresia (JIA). There was no significant trend in SIA, duodenal atresia or JIA prevalence over time (RR=1.0, 95% credible interval (CrI): 1.0 to 1.0 for each), but SIA and duodenal atresia prevalence varied by geographical location (p=0.03 and p=0.04, respectively). There was weak evidence of an increased risk of SIA in mothers aged less than 20 years compared with mothers aged 20 to 29 years (RR=1.3, 95% CrI: 1.0 to 1.8). Conclusion: This study found no evidence of a temporal trend in the prevalence of SIA, duodenal atresia or JIA, although SIA and duodenal atresia prevalence varied significantly between registers.